Endoscopic Findings in Patients Presenting with Dyspepsia (Journal of Nobel Medical College, 2025)
Background: Dyspepsia is one of the most frequently encountered complaints in Medicine department, representing a significant proportion of outpatient visits.  The objective of our study was to evaluate the endoscopic findings in patients presenting with dyspepsia.Materials and Methods: This descriptive, cross sectional study was conducted in the Department of Internal Medicine, Nobel Medical College Teaching Hospital from May, 2024 to April, 2025 after obtaining ethical clearance from the Institutional Review Committee. The sample size was calculated to be 320. Age, gender and clinical symptoms were assessed. Upper gastrointestinal endoscopy was performed in all patients, and a rapid urease test was done to detect Helicobacter pylori infection.Results: The mean age of the study population was 34±5.65 years. Out of 320 patients, 170 were males and 150 were females, with a slight male predominance (male to female ratio 1.13:1). The most common upper GI endoscopy finding was gastritis (40%) followed by duodenitis (20%), duodenal ulcer (10%) and gastric ulcer (5%). Normal UGI endoscopy findings was observed in 25% of the study population. Epigastric pain (44.37%) was the most common symptom followed by epigastric burning (25%), post prandial fullness (19.06%) and early satiety (11.56%). Rapid Urease Test (RUT) for Helicobacter pylori infection was positive in 66.87% of the study population.Conclusion: Gastritis was the most common upper gastrointestinal endoscopic finding in our study followed by duodenitis. Normal endoscopic finding was observed in one fourth of the study population.